Analisis Laporan Realisasi Anggaran untuk Menilai Kinerja Keuangan Pemerintah Provinsi Kalimantan Barat Menggunakan Konsep Value for Money - Oktavianty, Neti; Desyana, Gita; Kurniawan, Rudy (ITB AAS INDONESIA, 2024)
The objectives of this study are as follows: (1) To evaluate the performance of the Government of the Provinsi Kalimantan Barat from 2019 to 2022 using the concept of value for money, with a focus on the economic aspect; (2) To assess the government of the Provinsi Kalimantan Barat between 2019 and 2022 with the use of the value for cash concept, with an emphasis on the efficiency aspect; (3) To measure the performance by the Government in the West kalimantine province from 2019 until 2022 using a concept of valor for money and focusing on the effectiveness aspect. This study is a case study using a qualitative method, with data from the Laporan Realisasi Anggaran Pendapatan Dan Belanja of the Provinsi Kalimantan Barat during the period. The method of analysis used is descriptive analysis. The results of the research show that the kinerja Keuangan of the Provinsi kaliamntan Barat from 2019 to 2022, evaluated with the concept of value for money from the economic, efficiency, and efficiency aspects, is in the category of economic criteria, quite efficient, and highly effective.